Aerobic exercise intensity does not affect the anabolic signaling following resistance exercise in endurance athletes - Jones, T. W.; Eddens, L.; Kupusarevic, J.; Simoes, D. C. M.; Furber, M. J. W.; van Someren, K. A.; Howatson, G. (Scientific Reports, 2021)
This study examined whether intensity of endurance stimulus within a concurrent training paradigm influenced the phosphorylation of signaling proteins associated with the mTOR and AMPK networks. Eight male cyclists completed (1) resistance exercise (RES), 6 × 8 squats at 80% 1-RM; (2) resistance exercise and moderate intensity cycling of 40 min at 65% VO2peak, (RES + MIC); (3) resistance exercise and high intensity interval cycling of 40 min with 6 alternating 3 min intervals of 85 and 45% VO2peak (RES + HIIC), in a cross-over design. Muscle biopsies were collected at rest and 3 h post-RES. There was a main effect of condition for mTORS2448 (p = 0.043), with a greater response in the RES + MIC relative to RES condition (p = 0.033). There was a main effect of condition for AMPKa2T172 (p = 0.041), with a greater response in RES + MIC, relative to both RES + HIIC (p = 0.026) and RES (p = 0.046). There were no other condition effects for the remaining protein kinases assessed (p > 0.05). These data do not support a molecular interference effect in cyclists under controlled conditions. There was no intensity-dependent regulation of AMPK, nor differential activation of anabolism with the manipulation of endurance exercise intensity.